Functional and Motor Outcome 5 Years After Stroke Is Equivalent to Outcome at 2 Months. Issue 6 (June 2015) - Meyer, Sarah; Verheyden, Geert; Brinkmann, Nadine; Dejaeger, Eddy; De Weerdt, Willy; Feys, Hilde; Gantenbein, Andreas R.; Jenni, Walter; Laenen, Annouschka; Lincoln, Nadina; Putman, Koen; Schuback, Birgit; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Recovery of patients within the first 6 months after stroke is well documented, but there has been little research on long-term recovery. The aim of this study was to analyze functional and motor recovery between admission to rehabilitation centres and 5 years after stroke. Methods— This follow-up of the Collaborative Evaluation of Rehabilitation in Stroke Across Europe study, included patients from 4 European rehabilitation centres. Patients were assessed on admission, at 2 and 6 months, and 5 years after stroke, using the Barthel Index, Rivermead Motor Assessment Gross Function, Leg and Trunk function, and Arm function. Linear mixed models were used, corrected for baseline characteristics. To account for the drop-out during follow-up, the analysis is likelihood-based (assumption of missingness at random). Results— A total of 532 patients were included in this study, of which 238 were followed up at 5 years post stroke. Mean age at stroke onset was 69 (±10 SD) years, 53% were men, 84% had ischemic strokes, and 53% had left-sided motor impairment. Linear mixed model analysis revealed a significant deterioration for all 4 outcomes between 6 months and 5 years (P<0.0001). Scores at 2 months were not statistically significant different from scores at 5 years after stroke. Higher age (P<0.0001) and increasing stroke severity on admission (P<0.0001) negatively affected long-term functional and motor recovery. Conclusions— Five-year follow-up revealed deterioration in functional and motor outcome, with a return to the level measured at 2 months. Increasing age and increasing stroke severity negatively affected recovery up to 5 years after stroke.